2010
DOI: 10.1002/pts.886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sustainability impacts of packaging: the plastic carry bag dilemma

Abstract: Life cycle assessment (LCA) is used by practitioners and policy-makers to help them understand the sustainability impacts of packaging. LCA is useful because it quantifi es the impact of a product throughout its life cycle, from raw materials extraction through to disposal or recovery. However, it can only ever be one input to decisions about the design or procurement of packaging. LCA has limitations as a tool to measure environmental impact and it does not currently evaluate social or fi nancial impact. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 5 publications
0
109
0
Order By: Relevance
“…Even when sustainability is a main project driver, the analysis shows trade-offs between sustainability considerations and other product characteristics. Substantive trade-offs-addressing the contents of the development process [60]-are a fundamental element in development processes [25,62,75]. However, this research shows that sustainability is not an equally important substantive trade-off in development processes; it is currently merely regarded as an add-on to existing product-packaging development aspects, with a limited impact on decision-making processes.…”
Section: Sustainable Packaging Development Trade-offsmentioning
confidence: 83%
See 1 more Smart Citation
“…Even when sustainability is a main project driver, the analysis shows trade-offs between sustainability considerations and other product characteristics. Substantive trade-offs-addressing the contents of the development process [60]-are a fundamental element in development processes [25,62,75]. However, this research shows that sustainability is not an equally important substantive trade-off in development processes; it is currently merely regarded as an add-on to existing product-packaging development aspects, with a limited impact on decision-making processes.…”
Section: Sustainable Packaging Development Trade-offsmentioning
confidence: 83%
“…A generally applicable definition of sustainable packaging is difficult to identify [25,26]. Well-established are the definitions by the Sustainable Packaging Coalition (SPC) [27] and the Sustainable Packaging Alliance [28].…”
Section: Sustainable Packagingmentioning
confidence: 99%
“…The standard scientific approach of this subject is through life cycle assessment (LCA). 4,5 For examples of case studies on reducing the ecoburden, see Singh et al 6 and Bovea et al.…”
Section: Reducing the Eco-burdenmentioning
confidence: 99%
“…5 There are also alternative eco-burden indicators (often based on LCA) that have been tuned more to packaging optimization in business practice (e.g. see Wever, 8 Svanes et al 9 and Wever et al).…”
mentioning
confidence: 99%
“…James and Grant (2003) and Lewis, Verghese and Fitzpatrick (2010) found that polymer-based 'bags for life' have lower environmental impacts than all types of singleuse bags. Furthermore, they point out that degradable single-use bags have similar greenhouse and water pollution effects to traditional single-use (non-degradable) bags.…”
Section: Introductionmentioning
confidence: 99%